Japan : 2016 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2016)
This 2016 Article IV Consultation highlights that the economic growth of Japan has slowed owing to weak private consumption and sluggish investment and that inflation has lost its forward momentum. Although financial conditions remain accommodative, falling stock prices and the appreciation of the yen have resulted in a modest tightening. The outlook for growth and inflation remains subdued. The economy is expected to expand at a moderate pace of about 0.3 percent in 2016, before slowing to 0.1 percent in 2017, excluding the possible effect of the yet-to-be-adopted economic stimulus package.